Entrepreneurial Orientation and Small and Medium Enterprises (SMES) Performance in Lagos State, Nigeria - Ilesanmi, Oladele Ayodeji; Onikoyi, Idris Adegboyega; Badiru, Nafiu Isola (The Journal of Accounting and Management, 2022)
The main objective of every entrepreneur in any given economy is to improve the performance of the business. However, to achieve this goal require the combination of many business resources that work together. Some resources are tangible, while others are intangible resources needed by an organisation to improve performance if effectively deployed. This paper studied the impact of Entrepreneurial Orientation (EO) on the organisational performance of Small and Medium-Sized Enterprises (SMEs) in Lagos State, Nigeria, as well as the role of Market Orientation (MO) as a moderator on the relationship between Entrepreneurial Orientation and organsational performance. The study employed survey research design with the use of structured questionnaire. A simple random sampling technique was adopted, and 448 questionnaires were retrieved and analyzed from 520 administered questionnaires among SMEs in Lagos State, Nigeria. The results of the analysis revealed that the combination of five major drivers of EO (Innovativeness, Proactiveness, Risk-Taking. Autonomy and Competitive Aggressiveness) have significant impact on SMEs innovation in Lagos State, with an R2 of 0.986 and a Sig. 0.000. The study also revealed the moderating role of MO on the interaction between EO and SMEs performance to be significant at adjusted R2of 0.981, Sig. 0.000. The study recommended that Managers/Owners of SMEs should adopt all the five major drivers of EO in their business decision-making process. Also consider the need for the creation of marketing department or dedicated employee to take the marketing role, to drive competitive advantage, through innovation.